Egg corticosterone can stimulate telomerase activity and promote longer telomeres during embryo development. Issue 23 (3rd November 2020) - Noguera, José Carlos; da Silva, Alberto; Velando, Alberto
Abstract: It is often assumed that the transfer of maternal glucocorticoids (GCs; e.g., corticosterone or cortisol) to offspring is an inevitable cost associated with adverse or stressful conditions experienced by mothers. However, recent evidence indicates that maternal GCs may adaptively programme particular physiological and molecular pathways during development to enhance offspring fitness. In this context, an important mechanism through which maternal GCs may lastingly affect offspring phenotypic quality and survival is via effects on embryo telomerase activity and so on offspring postnatal telomere length. Here, using a field experimental design for which we manipulated the corticosterone content in yellow‐legged gull ( Larus michahellis ) eggs, we show that embryos from corticosterone‐injected eggs not only had a higher telomerase activity but also longer telomeres just after hatching. A complementary analysis further revealed that gull hatchlings with longer telomeres had a higher survival probability during the period when most of the chick mortality occurs. Given the important role that telomere length and its restoring mechanisms have on ageing trajectories and disease risk, our findings provide a new mechanistic link by which mothers may presumably shape offspring life‐history trajectories and phenotype.